1 1 1

-4 ----- x - 2 ---- = -----

3 3 4

-(4 1/3)x - 2 1/3 = 1/4

(4*3 + 1)x/3 - (2*3 + 1)/3 = 1/4

-13x/3 - 7/3 = 1/4

13x/3 + 7/3 = -1/4

(13x + 7) /3 = - 1/4

denominator is taken to the other side of the equation

13x + 7 = -3/4

7 is also taken to the other side of the equation inorder to find x

13x = -3/4 -7 = (-3 - (4*7))/4 = (-3 -28)/4

13x = -31/4

x = -31/(4*13)

x = -31/52

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up